Wildfire behaviour data for an experimental crown fire in thinned boreal black spruce, Alberta, Canada, 2019-05-11 - Thompson, Dan K (8062760) (2020)
Data describing an experimental forest fire in Wabasca, Alberta, Canada in May 2019. The fire is described in detail in the paper: "Recent Crown Thinning in a Boreal Black Spruce Forest Does Not Reduce Spread Rate nor Total Fuel Consumption: Results from an Experimental Crown Fire in Alberta, Canada" https://doi.org/10.3390/fire3030028